Economic development of Daghestan: cities and district capitals in post-reform period (2nd half of the xix - beginning of the xx century) - Gadzhi Magomedkamilovich Guseynov (Вестник Майкопского государственного технологического университета, 2023)
The study of reforms in Dagestan which contributed to the involvement of its peoples in the economic, political and cultural space of the Russian Empire using archival materials, first introduced into scientific circulation seems to be relevant. The problem is to study some previously unknown features of economic development, such as road construction; building bridges, construction of a seaport in Petrovsk on the Caspian Sea, laying of a railway linking Dagestan with Russia and the South Caucasus through the North Caucasus, which had both transport and industrial value. The attention is focused on the cities of Temir-Khan-Shura, Petrovsk, Derbent and Kizlyar, as well as the settlement of Khasavyurt, which played a large role in the socio-economic, political and cultural development of post-reform Dagestan. The aim of the study was to analyze main economic, political and cultural changes in the cities of Dagestan, which were conditioned by their integration into the capitalist path of development of Russia and colonial interests of autocracy. Cities, which made up an insignificant part of the oblast population in the post-reform time, played an increasing role in the socio-economic, political and cultural development of Dagestan. The problems set in the article were solved with the application of general scientific research methods within the framework of historical, comparative and statistical analysis. The results of the research allow for the conclusion that the post-reform period was a turning point in the history of Dagestan in many respects and, above all, that its entry into the Russian Empire determined the further economic progress of the entire North Caucasus. Gradually, the settled for centuries economic structure of the highlanders took the path of transformation under the influence of Russian market relations of the second half of the 19th century.